1998
DOI: 10.1002/(sici)1097-0215(19981109)78:4<430::aid-ijc7>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Dietary factors and risk of lung cancer in never‐smokers

Abstract: We studied dietary risk factors for lung cancer among never-smokers in a population-based case-control study in Stockholm, 1989Stockholm, -1995 The results regarding milk products could be consistent with dietary fat as a risk factor for lung cancer, although a more comprehensive assessment of fat intake is necessary to explore this relation. Int.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…There are few studies that adjusted for dietary factors and environmental exposures (such as second-hand smoke and occupational exposures). Although somewhat controversial, dietary factors such as red meat consumption, fat intake, and intake of fruits and vegetables have also been linked to lung cancer risk (47)(48)(49)(50)(51). Furthermore, consumption of a specific type of alcohol may be related to certain dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies that adjusted for dietary factors and environmental exposures (such as second-hand smoke and occupational exposures). Although somewhat controversial, dietary factors such as red meat consumption, fat intake, and intake of fruits and vegetables have also been linked to lung cancer risk (47)(48)(49)(50)(51). Furthermore, consumption of a specific type of alcohol may be related to certain dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…For 18 evaluated case-control studies on vegetable consumption, (129)(130)(131)(132)(133)135,137,139,140,143,145,147,(149)(150)(151)(152)(153)(154) the mean relative risk was 0.69 and the range was 0.30-1.49 (Fig. 20).…”
Section: Lungmentioning
confidence: 99%
“…Among women, consumption of milk may decrease risk of colorectal cancer (1) and cervical cancer (2), but have no effect on breast cancer e.g., (3)-4) or endometrial cancer (4). Results for lung cancer are quite mixed, with some studies suggesting risk reduction e.g., (5) or risk enhancement e.g., (6) that may vary by gender (7) or the histology of the tumor (8). A recent review on ovarian cancer concluded that consumption of low-fat milk is protective (9), but a pooled analysis of 12 cohort studies observed an elevated risk associated with increased lactose intake (10).…”
Section: Introductionmentioning
confidence: 99%